Clinical implication of complications on patient perceived health status following spinal fusion surgery. Issue 2 (February 2015) - Verla, Terence; Adogwa, Owoicho; Fatemi, Parastou; Martin, Joel R.; Gottfried, Oren N.; Cheng, Joseph; Isaacs, Robert E.
Abstract Approximately 2% to 16% of patients undergoing spinal surgery suffer adverse events or complications. There is a paucity of studies evaluating the impact of complications on long-term outcomes. The purpose of this study was to assess the long-term effects of surgical complications on patient functional improvement and overall health status, using a multi-institutional, prospective spine outcomes registry. A total of 1498 patients undergoing primary lumbar fusion for low back pain and/or radiculopathy between January 2003 and December 2010 were enrolled. All patients completed the Oswestry Disability Index (ODI), Medical Outcome Study Short Form 36 (SF-36), and back and leg pain numerical rating scores (Visual Analog Scale [VAS]) before surgery and at 1 and 2 years post-operatively. Patients were stratified based on the occurrence of a peri or post-operative complication, and by major versus minor complications. Baseline and 2 year clinical outcome scores were compared between cohorts. Both groups were similar at baseline. Complications occurred in 115 (7.68%) patients. The most common complications were cerebrospinal fluid leak (49.18%), bleeding requiring transfusion (13.11%) and nerve root injury (9.83%). Compared to baseline, there was no significant difference in the extent of functional improvement (ODI, VAS, SF-36) between both patient groups at 1 and 2 years post-operatively. Furthermore, there was no significant difference in outcome scores between patients with minor versus major complications. Within the context of an ongoing debate on the consequences of complications, we observed no lasting effect of complications on the patient's interpretation of overall health status and functional improvement at 1 and 2 years following elective lumbar spine surgery.